Indigenous compared with non-Indigenous Australian patients at entry to specialist palliative care: Cross-sectional findings from a multi-jurisdictional dataset - Woods, John A. (PLoS One, 2019)
BACKGROUND: There are few quantitative studies on palliative care provision to Indigenous Australians, a population known to experience distinctive barriers to quality healthcare and to have poorer health outcomes than other Australians. OBJECTIVES: To investigate equity of specialist palliative care service provision through characterising and comparing Indigenous and non-Indigenous patients at entry to care. METHODS: Using data (01/01/2010–30/06/2015) from all services participating in the multi-jurisdictional Palliative Care Outcomes Collaboration, Indigenous and non-Indigenous patients entering palliative care were compared on proportions vis-à-vis those expected from national statutory datasets, demographic characteristics, and entry-to-care status across fourteen ‘problem’ domains (e.g., pain, functional impairment) after matching by age, sex, and specific diagnosis. RESULTS: Of 140,267 patients, 1,465 (1.0%, much lower than expected from statutory data) were Indigenous, 133,987 (95.5%) non-Indigenous, and 4,905 (3.5%) had a missing identifier. The proportion of patients with a missing identifier diminished markedly over the study period, without a corresponding increase in the proportion identified as Indigenous. Indigenous compared with non-Indigenous patients were younger (mean 62.8 versus 73.0 years, p<0.001), a higher proportion were female (51.5% versus 46.3%; p<0.001) or resided outside major cities (44.2% versus 21.5%, p<0.001). Across all domains, Indigenous compared with matched non-Indigenous patients had lower or equal risk of status requiring prompt intervention. CONCLUSIONS: Indigenous patients (especially those residing outside major cities) are substantially under-represented in care by services participating in the nationwide specialist palliative care Collaboration, likely reflecting widespread access barriers. However, the similarity of status indicators among Indigenous and non-Indigenous patients at entry to care suggests that Indigenous patients who are able to access these services do not disproportionately experience clinically important impediments to care initiation.